Sikap Bahasa Masyarakat Desa Sukanegara Kabupaten Bogor Dalam Pemertahanan Bahasa Sunda - Iqbal Sidik; Lulu Lutfianingrum; Sinta Rosalina (Jurnal Ilmiah Wahana Pendidikan, 2023)
Regional languages ​​can be said to be a reflection of a speech community. Characteristics of language attitudes include language loyalty, language pride, and awareness of language norms. If the characteristics of language attitudes are still carried out by a group of people, then it can be said that the community has a positive attitude, otherwise if these characteristics disappear or weaken, then the community has a negative attitude. The approach in this study uses sociolinguistics which is a science that examines the variety of languages ​​that exist in social society. The method used is qualitative research. The subjects of this study were the people in Sukanegara Village, precisely in Jonggol District, Bogor Regency, totaling 22 people with an age range of 17-50 years. Meanwhile, the object of this study is language attitudes in the maintenance of Sundanese. The indicators that will become a research into the Language Attitudes of the Sukanegara Village Community in the Maintenance of Sundanese include aspects of language loyalty, language pride, and awareness of language norms. From the analysis conducted, it can be concluded that of the three characteristics of language attitudes, the respondents who are members of the Sukanegara village community have a positive attitude towards their regional language, namely Mother language. The people of Sukanegara village are loyal to Sundanese by using it in their family environment, peers and remain loyal to using Sundanese at certain moments in the world of work. The people of Sukanegara village are also proud of the Sundanese language they use and the answers disagree and strongly disagree are the most frequently chosen for the statement that Sundanese is an underdeveloped language. Then the last characteristic of language attitudes is the awareness of Sundanese norms which is analyzed based on the use of weak or harsh language in the Sundanese language used by the Sukanegara village community, the result is that the use of lemes Sundanese is dominated by the use of the word limbs and social interaction.